Les Blocs d'estran a Saint-Fabien-Sur-Mer, Estuaire Maritime du Saint-Laurent, Quebec - Dionne, Jean-Claude (Atlantic Geology)

(untitled) (Maritime Sediments Editorial Board, 1979)
ABSTRACT Various boulder accumulations occur at Mercier Cove, Saint-Fabien-sur-Mer, on the south shore of the Lower St. Lawrence Estuary. Boulders, up to S m in diameter, are found on marine postglacial deposits of thick clay. The boulders are composed of two main lithologies: Precambrian igneous and metamorphie rocks from the Laurentidian Shield over 25 km to the north, and Paleozoic sedimentary rocks from the surrounding Appalachian ridges and shore platforms. Of the 9900 boulders counted throughout the tidal zone, 57% are Laurentidian rocks and 43% Appalachian. As there is no evidence of glacial drift in the area, and as the boulders overlay fine marine sediments of postglacial age, drift ice can be considered as the principal agent of transportation and deposition.